2006
DOI: 10.1159/000091683
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a New Parenteral Lipid Emulsion (SMOFlipid) in Surgical Patients: A Randomized, Double-Blind, Multicenter Study

Abstract: Background/Aims: A new lipid emulsion based on soybean oil, medium chain triglycerides, olive oil and fish oil (SMOFlipid) was tested for safety, tolerance, metabolic and clinical efficacy in surgical patients. Methods: In a prospective, double-blind European multicenter study, postoperative patients (elective abdominal or thoracic surgery) were randomized to receive isonitrogenous, isoenergetic (30–35 kcal/kg) total parenteral nutrition over 5 postoperative days including either SMOFlipid® 20% or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 41 publications
7
102
1
4
Order By: Relevance
“…18 An example of such a preparation is SMOFlipid, an emulsion containing soya bean, medium chain triglycerides, olive and fish oil, yielding an improved ratio of omega 3 and 6 fatty acids, which, in the acute, post-operative setting, has been associated with a better hepatic tolerance and reduced length of hospital stay. 19 Further evidence is needed to assess the advantages and disadvantages of alternative lipid emulsions in longer term HPN. Electrolytes can be delivered either in commercially available carbohydrate and amino acid solutions or may be added to PN formulations to meet individual requirements.…”
Section: Parenteral Nutrition Formulationsmentioning
confidence: 99%
“…18 An example of such a preparation is SMOFlipid, an emulsion containing soya bean, medium chain triglycerides, olive and fish oil, yielding an improved ratio of omega 3 and 6 fatty acids, which, in the acute, post-operative setting, has been associated with a better hepatic tolerance and reduced length of hospital stay. 19 Further evidence is needed to assess the advantages and disadvantages of alternative lipid emulsions in longer term HPN. Electrolytes can be delivered either in commercially available carbohydrate and amino acid solutions or may be added to PN formulations to meet individual requirements.…”
Section: Parenteral Nutrition Formulationsmentioning
confidence: 99%
“…Clinical studies have shown that fat emulsions containing a mixture of soya, coconut, olive and fish oil result in less cholestasis, particularly in children (16). Randomised studies of SMOF lipids in connection with chronic intestinal failure are taking place in Europe and the USA (17).…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective studies have been published assessing the preventive effect of IVLEs containing FO on alterations in LETs or PNALD (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Characteristics of these studies are shown in table I.…”
Section: Potential Benefits Prevention Of Alterations In Liver Enzymementioning
confidence: 99%
“…Prospective studies collecting data on plasma clearance of IVLEs containing FO are presented in table II (6)(7)(8)(12)(13)(14)16,17,(19)(20)(21)(30)(31)(32)(33)(34).…”
Section: Plasma Lipid Clearancementioning
confidence: 99%